2005
DOI: 10.1007/s00436-005-0031-9
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining hyperimmune anti-Cryptosporidium parvum ovine colostrum. A study of the humoral immune response in immunized sheep

Abstract: Three ewes were immunized five times over a 2-month period prior to giving birth by intramuscular injection, oral administration and intramammary infusion of antigen and viable or freeze-dried Cryptosporidium parvum oocyst solution emulsified with Freund's complete and incomplete adjuvant. Two animals served as controls and another two as adjuvant controls. Serum was collected at first immunization and thereafter every 2 to 4 weeks. Colostrum and milk were collected as well. All samples were assayed for C. par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…In the current study, subcutaneous prime immunisation with antigen in FA yielded significantly higher overall anti-HA antibody titres when compared to intraperitoneal prime. These findings are in contrast to an earlier study which demonstrated that anti- C. parvum antibody titres at parturition [45] were sixteen-fold higher in the serum when sheep received intraperitoneal immunisation compared to intramuscular immunisation. Furthermore, at twenty days post-lambing, detectable anti- C .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the current study, subcutaneous prime immunisation with antigen in FA yielded significantly higher overall anti-HA antibody titres when compared to intraperitoneal prime. These findings are in contrast to an earlier study which demonstrated that anti- C. parvum antibody titres at parturition [45] were sixteen-fold higher in the serum when sheep received intraperitoneal immunisation compared to intramuscular immunisation. Furthermore, at twenty days post-lambing, detectable anti- C .…”
Section: Discussioncontrasting
confidence: 99%
“…The route of immunisation has been shown to influence the nature and intensity of the immune response generated to an antigen [29], [45], [46]. In the current study, subcutaneous prime immunisation with antigen in FA yielded significantly higher overall anti-HA antibody titres when compared to intraperitoneal prime.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…and Giardia spp. are commonly isolated from sheep faeces (Abd-El-Wahed 1999;Chalmers et al 2002;Alonso-Fresan et al 2005;Ryan et al 2005;Martin-Gomez et al 2006;Santin et al 2007). The non-zoonotic Giardia assemblage E is most commonly found, with few reports of the zoonotic assemblages A and B being isolated (Santin et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Having high concentration of Igs in colostrum, would help in improving the immune status of lambs feeding on the colostrum, as a result lambs would have enough immunity especially in the first 3 weeks of age, until their immune system becomes fully activated. It is, therefore, essential to increase the quality of the colostrum to increase the survival rate of newborn lamb because colostrum is the only source of antibodies (Martín-Gómez et al, 2006).…”
Section: Resultsmentioning
confidence: 99%